Differential aspects between cobalt-chromium everolimus drug-eluting stent and Absorb everolimus bioresorbable vascular scaffold: From bench to clinical use - Yohei Sotomi (2018)
© 2015 Informa UK, Ltd. Drug-eluting stents have significantly improved the outcomes of percutaneous coronary intervention by substantially reducing in-stent restenosis and stent thrombosis. However, a potential limitation of these stents is the permanent presence of a metallic foreign body within the artery, which may cause vascular inflammation, restenosis, thrombosis, neoatherosclerosis, permanent impairment of the physiological vasomotor function and interference with potential future grafting of the stented segment. Bioresorbable scaffolds have the potential to overcome these limitations as they provide temporary scaffolding and then disappear, liberating the treated vessel from its cage and restoring pulsatility, cyclical strain, physiological shear stress and mechanotransduction. This article presents a comparison between the most widespread bioresorbable vascular scaffold 'Absorb BVS' and second-generation drug-eluting stent (cobalt chromium everolimus-eluting stent) from bench to clinical use.